2013
DOI: 10.1002/jps.23386
|View full text |Cite
|
Sign up to set email alerts
|

Development of Imiquimod-Loaded Mucoadhesive Films for Oral Dysplasia

Abstract: Oral squamous dysplasia, which can usually be readily visualized as leukoplakia during an oral examination and confirmed by histology, is often considered a premalignant condition. Current treatments, however, focus on the final stages of disease, and treatments such as surgery can lead to postoperative disabilities. Hence, this study was designed to develop a noninvasive, mucoadhesive drug delivery system loaded with an immune response modifier, imiquimod, as treatment for precancerous dysplastic lesions. Ble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 34 publications
1
34
0
Order By: Relevance
“…Although previous work showed that 1:2 PVP:CMC mucoadhesive films lasted 4 hr submerged in sink conditions in vitro and achieved sustained release for up to 3 hr, 7 several other film properties were not reported, such as adhesiveness of film to mucosal surface, mechanical properties for better handling, and swelling, which determines the release mechanism. All of these characteristics will play key roles in the design of a successful, bioerodible, mucoadhesive drug delivery system.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Although previous work showed that 1:2 PVP:CMC mucoadhesive films lasted 4 hr submerged in sink conditions in vitro and achieved sustained release for up to 3 hr, 7 several other film properties were not reported, such as adhesiveness of film to mucosal surface, mechanical properties for better handling, and swelling, which determines the release mechanism. All of these characteristics will play key roles in the design of a successful, bioerodible, mucoadhesive drug delivery system.…”
Section: Discussionmentioning
confidence: 96%
“…6 A mucoadhesive system loaded with an immune response modifier, imiquimod, for potential local treatment of precancerous oral lesions was previously developed. 7 Use of this delivery system would offer advantages of a non-invasive approach and reduced systemic effects of drugs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…199 Ramineni et al studied cyclodextrins for the inclusion of imiquimod to treat precancerous dysplastic lesions of the oral cavity. 200 This group developed a mucoadhesive film for the conveyance of a highly hydrophobic drug. To prepare these films, a polymer aqueous solution of polyvinylpyrrolidone mixed with ethanol following the addition of propylene …”
Section: Complexes Of Cyclodextrinsmentioning
confidence: 99%
“…Several other researchers are exploring the use of mucoadhesive drug delivery systems for chemoprevention of oral cancer [87,88]. Cid et al [89] explored chitosan gels for buccal delivery of the highly lipophilic celecoxib, a COX-2 inhibitor, for oral cancer chemoprevention.…”
Section: Oral Cancermentioning
confidence: 99%